Myt och vetenskap om kastration av tik - Boëthius, Hanna (2011)
This is a literature study in which I investigate if there are scientific studies that form the basis of the Swedish dog world views concerning the spaying of bitches. The positive impacts are said to be reduced problems with pseudopregnancy, reduced risk of pyometra, reduced risk of mammary and uterine tumors, an earlier cease of bone growth, a more active and happier dog and a bitch who is more tolerant of other dogs. The negative consequences are said to be urinary incontinence, increased aggressiveness, lower metabolism and the increased risk of obesity, a more lethargic individual and altered coat. There are studies indicating that spaying reduces behavioral problems associated with heat and pseudopregnancy. Assuming no ovary tissue persists after the procedure, and there is no progesterone production, the risk of pyometra decreases. Early spaying, before the first heat, reduces the risk of mammary tumors. Spaying also reduces the risk of uterine tumors, but there are no studies that suggest that you get a happier dog ore that she would be more tolerant of other dogs, rather the opposite. Many studies show that it is common for spayed bitches to suffer from urinary incontinence. The reason is the change in proportion between collagen fibers and smooth muscle cells of the urethra, leading to impaired bladder control. There are different views of why this occurs. It is also disputed if spaying has any effects on the aggressiveness of the bitch. An increased reactivity has been documented in several studies and the idea that the bitch would become more lethargic is a myth. Metabolism is thought to decrease and the bitch may have easier to develop overweight, but this is a subject of dispute. Coat changes may occur, but it does not affect all castrated bitches.